Benefit–risk assessment and reporting in clinical trials of chronic pain treatments: IMMPACT recommendations. Issue 6 (9th June 2022) - Kleykamp, Bethea A.; Dworkin, Robert H.; Turk, Dennis C.; Bhagwagar, Zubin; Cowan, Penney; Eccleston, Christopher; Ellenberg, Susan S.; Evans, Scott R.; Farrar, John T.; Freeman, Roy L.; Garrison, Louis P.; Gewandter, Jennifer S.; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract: Chronic pain clinical trials have historically assessed benefit and risk outcomes separately. However, a growing body of research suggests that a composite metric that accounts for benefit and risk in relation to each other can provide valuable insights into the effects of different treatments. Researchers and regulators have developed a variety of benefit–risk composite metrics, although the extent to which these methods apply to randomized clinical trials (RCTs) of chronic pain has not been evaluated in the published literature. This article was motivated by an Initiative on Methods, Measurement, and Pain Assessment in Clinical Trials consensus meeting and is based on the expert opinion of those who attended. In addition, a review of the benefit–risk assessment tools used in published chronic pain RCTs or highlighted by key professional organizations (ie, Cochrane, European Medicines Agency, Outcome Measures in Rheumatology, and U.S. Food and Drug Administration) was completed. Overall, the review found that benefit–risk metrics are not commonly used in RCTs of chronic pain despite the availability of published methods. A primary recommendation is that composite metrics of benefit–risk should be combined at the level of the individual patient, when possible, in addition to the benefit–risk assessment at the treatment group level. Both levels of analysis (individual and group) can provide valuable insights into the relationship between benefits and risks associated with specific treatments across different patient subpopulations. The systematic assessment of benefit–risk in clinical trials has the potential to enhance the clinical meaningfulness of RCT results.